Implementation of the teaching industry as a strategy for developing digital marketing competencies for diploma in graphic design students at the malaka hotel - Pertiwi, Annisa Bela; Masunah, Juju; Prawira, Nanang Ganda; Karyono, Tri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The digital marketing industry in the hospitality sector needs a creative workforce that is able to integrate technical skills with strategic innovation. The Teaching Industry program implemented by the Graphic Design Study Program of Widyatama University in collaboration with Hotel Malaka is designed to overcome the gap between the competencies of graphic design students and industrial needs. This research aims to evaluate the implementation of the Teaching Industry program in developing the technical competence of Diploma 4 Graphic Design students through various learning approaches. The research uses a descriptive qualitative method with data collection techniques in the form of in-depth interviews, participatory observations, and document analysis (logbook, portfolio, and performance evaluation). The study involved 17 students working on digital marketing projects, including content planning, graphic design, photography, videography, and social media management during the Odd Semester 2022-2023 to the Odd Semester 2024-2025. The results of the study show that 80% of students have experienced an increase in technical competence, especially in producing visual content, branding strategies, and social media management. Performance evaluation showed that branding design obtained the highest score (86.8), followed by event content creation (85.6). Work-Based Learning, Experiential Learning, Collaborative Learning, and Project-Based Learning approaches have proven to be effective in supporting student skill development. This program has successfully prepared students for the world of work in the creative industry sector, especially digital marketing. This Teaching Industry learning model can be adopted by other educational institutions to answer the industry's need for skilled and innovative creative workers.